High power Tesla driven miniature plasma opening switch - Rajesh Kumar (2009)
The plasma opening switch (POS) is used in pulsed power systems where a very fast opening and high current switch is required. Plasma is injected into the switch, which carries a large conduction current, before it opens in a process that lasts for a few nanosecond and transfers the current to a parallel-connected load at a much increased voltage and with a much shorter rise time. The conduction and opening times of the switch are dependent on plasma parameters such as the distribution, speed and species, all of which are determined by the plasma source. Most of the earlier reported work involves large dimension POSs and a correspondingly high input current (more than 100 kA) and uses carbon plasma. One main objective of the present research was to achieve a low input current (20 kA) and miniaturised POS by using hydrogen plasma rather than carbon plasma on account of its lower mass. A cable gun was selected for producing the plasma, since although this produces both hydrogen and carbon plasma these arise different times during its operation. For the present application a Tesla transformer was used in preference to a Marx generator to produce an initial high voltage pulse for the system, on the basis of its simpler design and cost effectiveness. This transformer together with an associated water PFL (pulse forming line) and pressurised switch was capable of producing a load current in excess of 20 kA with a rise time of 53 ns, which was fed through the POS to the final load. Special diagnostics arrangements were necessary to measure the fast high current and voltage pulse a in nonintrusive way. Faraday cups and a high speed camera were used to measure the plasma parameters. The overall system built (i.e. including the POS) is capable of producing a 22 kA current with a rise time of 5 ns, and of generating a power of more than 10 GW. Much of the work detailed in the thesis has already been presented in peer reviewed journals and at prestigious international conferences.